Allocation of home care services by municipalities in Norway: a document analysis - Holm, Solrun; Mathisen, Terje Andreas; Sæterstrand, Torill Margaret; Brinchmann, Berit Støre (BMC Health Services Research, 2017)
Source at http://dx.doi.org/10.1186/s12913-017-2623-3 Background: In Norway, elder care is primarily a municipal responsibility. Municipal health services strive to offer the ‘lowest level of effective care,’ and home healthcare services are defined as the lowest level of care in Norway. Municipalities determine the type(s) of service and the amount of care applicants require. The services granted are outlined in an individual decision letter, which serves as a contract between the municipality and the home healthcare recipient. The purpose of this study was to gain insight into the scope and duration of home healthcare services allocated by municipalities and to determine where home care recipients live in relation to home healthcare service offices. Methods: A document analysis was performed on data derived from 833 letters to individuals allocated home care services in two municipalities in Northern Norway (Municipality A = 500 recipients, Municipality B = 333 recipients). Results: In Municipality A, 74% of service hours were allotted to home health nursing, 12% to practical assistance, and 14% to support contact; in Municipality B, the distribution was 73%, 19%, and 8%, respectively. Both municipalities allocated home health services with no service end date (41% and 85% of the total services, respectively). Among recipients of “expired” services, 25% in Municipality A and 7% in Municipality B continued to receive assistance. Conclusions: Our findings reveal that the municipalities adhered to the goal for home care recipients to remain at home as long as possible before moving into a nursing home. The findings also indicate that the system for allocating home healthcare services may not be fair, as the municipalities lacked procedures for revising individual decisions. Our findings indicate that local authorities should closely examine how they design individual decisions and increase their awareness of how long a service should be provided.